Microwave-assisted Sustainable Production of Biodiesel: A Comprehensive Review - Ao, Supongsenla; Chhandama, Michael V.; Li, Hu; Lalthazuala Rokhum, Samuel (Current Microwave Chemistry, 2023)
Limited crude petroleum and growing awareness of fossil fuel depletion have enabled the development of alternative fuels and new energy sources. Biodiesel, also known as fatty acid methyl esters (FAME), has received a lot of attention due to its biodegradability, renewability, cost effective and nontoxicity. The purity of biodiesel production and uniform heating are the major hurdles for large scale biodiesel production. Recent microwave energy-based heating method has proved the potential for cleaner chemical production, short time duration, uniform heating, and purity over conventional heating method. The goal of this review is to discuss the biodiesel production using microwave-assisted heating. The different feedstocks used for biodiesel production, effects of microwave irradiation, factors affecting the rate of microwave-assisted transesterification to produce biodiesel were comprehensively discussed. Microwave irradiation has been compared to other technologies aiming to enhance the efficiency of overall process. The primary knowledge gaps in biodiesel production can be identified based on this research, ensuring the biodiesel industry's longterm sustainability.
Keywords: catalysis